A Preliminary Study On Biological Nitrogen Removal Process For Local Drinking Water Treatment - Wong, Eng Cheong (2021)
Greatly input of phosphorus (P) and nitrogen (N) into the water bodies from human activities have caused the arising of eutrophication globally. Limitations of the conventional drinking water treatment processes in removing N has brought the biological nitrogen removal (BNR) to the light and is widely recognized in developed countries with temperate climate. However, knowledge and expertise on the application of this biological treatment process is relatively limited in developing countries, so as Malaysia in tropical region. Thus, this research aims to provide a preliminary study on the establishment of the BNR process for drinking water treatment in the local context. In the first stage of this study, a lab scale sequencing batch reactor (SBR) fed with synthetic river water and seeded with different seeding sources was operated for the establishment of BNR process. The cultivation period and performance from non-BNR sludge to BNR sludge were studied. The results showed that the SBR seeded solely with activated sludge collected from sewage treatment plant was more promising in terms of N removal after four weeks of cultivation. In the second stage of this study, a new SBR seeded with the earlier cultivated sludge was operated to investigate the effect of influent chemical oxygen demand (COD) concentration and preanoxic/postanoxic condition on the BNR process performance. From the results, at the influent COD concentration of 45 mg/L in postanoxic condition, the final concentrations of both the COD and NH4+-N were at 2 mg/L and 5 mg/L respectively. In the final stage, the stability and robustness of the process were examined. It showed that the BNR performance was consistent during the prolonged SBR operation with mixed liquor suspended solid (MLSS) and mixed liquor volatile suspended solid (MLVSS) of about 1720 mg/L and 1630 mg/L respectively as well as sludge volume index (SVI) of about 85 mL/g were stably maintained. The robustness of the process was also observed when the system rapidly recovered from an operational failure. These findings suggest that the establishment of BNR process for drinking water treatment is feasible in Malaysia.